Investigation of early mussel (Perna canaliculus) development using histology, SEM imaging, immunochemistry and confocal microscopy. Issue 3 (16th March 2017) - Rusk, Adam B.; Alfaro, Andrea C.; Young, Tim; Watts, Ellie; Adams, Serean L.
ABSTRACT: A comprehensive study, incorporating histology, light microscopy, scanning electron microscopy, immunochemistry and confocal microscopy, was performed to investigate embryogenesis and larval development of the New Zealand Greenshell™ mussel, Perna canaliculus. Detailed observations with this multi-technique approach revealed a gastrula stage at 18 hours post-fertilization, with the appearance of a blastopore, apical sense organ and enclosing vegetal pole. Early D-stage larvae showed limited alimentary organogenesis and clear initiation of a developing nervous system. Shell morphology of D-larvae was characterized by a flat, hinged, pitted–punctate prodissoconch I shell, followed closely by commarginal growth lines within the prodissoconch II shell. Early umbo larvae had a protruding functioning velum, and well-developed posterior adductor and velar retractor muscles. Significant progression in neuronal development occurred just before the umbo stage with noticeable paired cerebral, pedal and visceral ganglia. Shell morphology was characterized by further prodissoconch II secretion with a more rounded umbonate appearance. During the transition through the pediveliger stage, rapid development of the gill rudiment, eye spot and functioning foot was observed with ongoing neuronal development. The first appearance of the dissoconch shell layer took place during this transition, at which point the nervous system was highly distinct with innervations extending throughout muscle regions and between ganglia. This study provides the first comprehensive documentation of the developmental stages of P. canaliculus larvae from fertilization to settlement. The study highlights the advantages of using a combination of techniques to understand larval development and provides crucial information to identify larval performance during larval rearing.